PENGARUH DIGITAL CULTURE TERHADAP ALQURAN PERSPEKTIF KEBUDAYAAN - Nahdaturrahmi Nahdaturrahmi; Muhammad Taufiq (CV. Adiba Aisha Amira, 2025)
Digital culture has changed the way Muslims interact with the Qur'an. The influence of digital culture on the understanding and practice of the Qur'an from a cultural perspective. This article uses qualitative methods, investigating how social media, religious apps, and other digital platforms influence the interpretation, dissemination, and application of the teachings of the Qur'an in daily life. The results show that digital culture plays a significant role in shaping Islamic behaviour and values, and offers new opportunities for da'wah and Islamic education. However, there is still a challenge in maintaining the authenticity and integrity of the teachings of the Qur'an amidst the swift flow of digital information. The findings provide new insights into how the Qur'an can be effectively integrated in the modern digital ecosystem, while maintaining authentic Islamic cultural values